KORELASI ANTARA TINGKAT PENGGUNAAN GADGET DENGAN HASIL BELAJAR KOGNITIF SISWA PADA MATA PELAJARAN IPAS DI KELAS V SDN KEMAKMURAN I - Firda Nurfadilah; Rana Gustian Nugraha; Nurdinah Hanifah (Jurnal Pendidikan Dasar, 2026)
With the advancement of the digital age, the use of gadgets among elementary school students has been on the rise, leading to various impacts on the learning process. The research problem is the large number of children who are allowed to own gadgets and use them excessively. This study aims to determine whether there is a correlation between gadget use and the cognitive learning outcomes of elementary school students in the 5th-grade IPAS subject at SDN Kemakmuran I. This study employs a quantitative approach using a correlational method. The study population consists of all 5th-grade students at SDN Kemakmuran I (n=26), with a total sampling technique used for data collection. Data on gadget usage were collected through a questionnaire, while data on cognitive learning outcomes were obtained from documentation of students’ End-of-Semester Assessment. Data analysis was conducted using Spearman’s rho correlation test with the assistance of SPSS 16 for Windows. The results of the study indicate that there is no significant relationship between the level of gadget use and students’ cognitive learning outcomes in the IPAS subject, as indicated by the significance value (ρ > 0.05). In addition, a correlation coefficient value of -0.272 was obtained, indicating that the correlation between the two variables is weak and negative. These findings suggest other factors play a more dominant role in determining cognitive learning outcomes